KAJIAN PENERAPAN MODEL ROLE PLAYING PADA PEMBELAJARAN SATUA BALI 'SIAP SELEM' - I Wayan Sujana; Ida Bagus Yoga Swadnyana; Putu Angelina Venia Putri Tama; Ni Komang Ristia Dewi; Ni Koming Devy Masyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the application of the role playing model in learning Balinese traditional stories (satua), specifically the story of 'Siap Selem' (The Black Rooster). The main purpose of this study is to analyze the theoretical foundations of role playing in elementary education, review relevant previous research findings, and assess the suitability of this model for teaching moral values embedded in Balinese satua. This research employs a qualitative literature review approach, systematically collecting data from academic journals, books, and scholarly reports published between 2015 and 2024. Data were analyzed through content analysis and thematic synthesis. The results indicate that role playing effectively stimulates students' critical thinking, empathy, and moral understanding when applied to cultural narratives. 'Siap Selem' contains rich moral themes—loyalty, courage, and justice—that align well with the affective and social learning objectives of the role playing model. Previous studies confirm that the integration of local cultural content into role playing activities significantly improves student engagement and character development. This study concludes that role playing is a highly suitable and contextually meaningful method for teaching Balinese satua at the elementary level, providing both cultural preservation and holistic student development.